BATU NISAN DI SITUS BINANGA SEBAGAI INDIKASI PEMUKIMAN MUSLIM KUNO DI PANTAI BARAT ACEH - Husni, Amir; Ismail, Sanusi; Nasruddin AS, Nasruddin AS; Abubakar, Bustami; Idria, Reza; Hermansyah, Hermansyah; Ruhamah, Ruhamah; Al Fairusy, Muhajir (Paradigma: Jurnal Kajian Budaya, 2024)
This article aims to discuss the development of ancient Muslim settlements on the west coast of Aceh based on the findings of Islamic gravestones at the Binanga site in Subulussalam City, Aceh. This site is very unique, it is located inland and right on the banks of the Singkel River, which is connected to the highlands of Sumatra. There are 131 Islamic gravestones, and their shapes vary greatly. The results of the morphological analysis show that the gravestones were divided into two groups: Aceh gravestones (batu Aceh) and Barus gravestones (nisan Barus). There are no biographical inscriptions carved on the gravestones, however, the morphological analysis shows that these gravestones date from the 18th to 19th centuries AD. These tombstones indicate that Muslim communities began to settle permanently in the interior of Aceh's west coast in the 1700s. The emergence of these settlements is related to the migration of people from the highlands of Sumatra to the west coast of Aceh, which was motivated by the development of international trade centered in Singkel and its surroundings since the 18th and 19th centuries AD. Thus, the tombstone on this site is very important because gave the clear picture to understand the emergence of Muslim settlements on the west coast of Aceh in the past.